Systematic review of reviews of observational studies of school-level effects on sexual health, violence and substance use. (May 2016) - Shackleton, Nichola; Jamal, Farah; Viner, Russell; Dickson, Kelly; Hinds, Kate; Patton, George; Bonell, Chris
Abstract: For three decades there have been reports that the quality of schools affects student health. The literature is diverse and reviews have addressed different aspects of how the school environment may affect health. This paper is the first to synthesise this evidence using a review of reviews focusing on substance-use, violence and sexual-health. Twelve databases were searched. Eleven included reviews were quality-assessed and synthesised narratively. There is strong evidence that schools' success in engaging students is associated with reduced substance use. There is little evidence that tobacco-control policies and school sexual-health clinics on their own are associated with better outcomes. Highlights: Schools are a key setting for improving adolescent health. There is strong evidence of school effects on smoking, drinking alcohol and drug use. There is little evidence for the effectiveness of tobacco control policies. There is little evidence for the effectiveness of school based sexual health clinics.